Low Health Literacy: A Devious Enemy of Patient Treatment Adherence - Mohiuddin, Abdul Kader (International Journal of Pharmaceutical & Biological Archive, 2022)
To access, comprehend, and use information to make decisions about their health, people must possess certain personal traits and social resources, which are referred to as health literacy. Patients’ ability to engage in complex disease management and self-care is strongly related to their level of health literacy. It can help us stay healthy by preventing illness and effectively managing existing illnesses. Personal health literacy refers to a person’s ability to locate, comprehend, and apply information and services to support health-related decisions and actions for themselves and others. The World Health Organization recommends health literacy as a tool for achieving several key targets outlined in the sustainable development goals. Low health literacy (LHL) is most commonly associated with mature patients with chronic health conditions who have limited education and are not necessarily from a lower income group. Furthermore, being literate in general does not imply being literate in health. People with limited health literacy may find it difficult to manage their condition and prevent illness, which may lead to increased use of health-care services. Furthermore, LHL is associated with increased hospitalizations, increased use of emergency care, decreased use of preventative services, and a worsened ability to understand labels and health messages, a worsened state of health, higher mortality, and more expensive medical care. Health literacy improves a population’s ability to care for themselves and aids in the reduction of health disparities. It has an impact on the use of health services, as well as on patient satisfaction and the physician-patient relationship. It is one of the major impediments to healthcare professionals adequately transmitting information to those under their care. Despite the negative implications of LHL, physicians are typically unaware of their patients’ health literacy levels and their subsequent effects on their patients’ outcomes.